Management of Anaphylactic Shock - Aisyah, Aisyah; Susilo, Susilo (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the management of anaphylactic shock highlights a critical need for immediate and effective interventions to mitigate the potentially fatal consequences of this medical emergency. Literature Review: The literature underscores the necessity of comprehensive patient education and the development of written emergency treatment plans, particularly for individuals at risk of severe allergic reactions. This proactive approach is vital for effective anaphylaxis management, as it empowers patients and caregivers to recognize symptoms and respond appropriately. The emphasis on having multiple epinephrine auto-injectors available is also crucial, given that some patients may require repeated doses during an anaphylactic episode. Conclusion: The significance of accurate diagnosis and triage grading in emergency treatment is also emphasized, as misdiagnosis can lead to inadequate treatment and potentially fatal outcomes (Dondi et al., 2022) . Collectively, these articles illustrate that while progress has been made in understanding and managing anaphylaxis, ongoing challenges persist that require a concerted effort from healthcare professionals, patients, and the broader community to enhance educational initiatives and improve emergency response capabilities.